Silk. [videorecording (DVD)] Season two - Moffat, Peter, 1962-; Stuke, Neil; Penry-Jones, Rupert, 1970- (BBC, 2015)
Martha Costello (Maxine Peake, The Village) returns to Shoe Lane Chambers having earned "silk." Now as a new member of the Queen's Counsel, Martha finds the stakes higher than ever as she faces Shoe Lane's newest prosecution barrister. As the pressure rises, so does the romantic tension between her and fellow barrister, Clive Reader (Rupert Penry-Jones, MI5). Meanwhile, Senior Clerk Billy Lamb (Neil Stuke, Inspector Lewis) turns to an unsavory solicitor for work, putting Martha's beliefs and standings to the test.